The Situation of the Egyptian Press on the March 1991 Uprising in Iraqi Kurdistan - SaeZayeded, Mahmoud (Humanities Journal of University of Zakho, 2022)
Egypt was not far from the events and results of the March 1991 uprising in Iraqi Kurdistan; It was close to it geographically, politically and militarily with the presence of the Egyptian forces in the Gulf region after Saddam Hussein’s aggression against Kuwait in August 1990 and its participation of the international coalition forces in the liberation of Kuwait that led by the United States of America in what was known as "Desert Storm". This was evident in the statements of President Mohamed Hosni Mubarak and in the statements of the Egyptian Foreign Ministry which calls for respect for rights, the rule of law, and the consolidation of the pillars of democracy around that all the national components of the Iraqi people rally. This case was translated by the Egyptian governmental and non-governmental press starting with the outbreak of the Kurdish uprising after the Cologne Conference in Germany on March 1, 1991, which aimed to unify the efforts of the two parties (the Kurdistan Democratic Party and the Patriotic Union of Kurdistan) and to return to the struggle to achieve autonomy for the region of Southern Kurdistan. The Egyptian press also followed the Peshmerga military operations to liberate Kurdish cities, such as Erbil, Sulaymaniyah, Kirkuk and Dohuk, besides, the news, announcements and statements issued in this regard by both the Iraqi and Kurdish sides, and then the Iraqi forces, especially the air force, struck the uprising and forced the Kurds to migrate to both the Iranian and Turkish borders which is so-called as the migration of millions, plus, the subsequent humanitarian tragedies that led to the intervention of the Security Council with the issuance of Resolution 688 on the first of April 1991 to establish a safe area for the Kurds north of the 36th parallel, and then holding parliamentary elections for the Kurdish autonomous region in May 1992. The purpose of the research is to monitor and analyze the position of the Egyptian press on this uprising and its results, including what it used to publish the statements of Egyptian officials about it, and what it used in its news, articles, angles of opinion and caricatures, in addition to the meetings it conducted with important Kurdish and Iraqi leaders at the time; In the end, we can form a comprehensive idea of the Egyptian situation through its internal, Arab and international dimensions, as well as explaining this and its impact on Egypt’s relations during the nineties of the last century, not only with the Kurds and Iraqis, but on its relations with the entire region.